2009
DOI: 10.1002/jms.1690
|View full text |Cite
|
Sign up to set email alerts
|

Generation of gas‐phase sodiated arenes such as [(Na3(C6H4)+] from benzene dicarboxylate salts

Abstract: Upon collision-induced activation, gaseous sodium adducts generated by electrospray ionization of disodium salts of 1,2- 1,3-, and 1,4-benzene dicarboxylic acids (m/z 233) undergo an unprecedented expulsion of CO(2) by a rearrangement process to produce an ion of m/z 189 in which all three sodium atoms are retained. When isolated in a collision cell of a tandem-in-space mass spectrometer, and subjected to collision-induced dissociation (CID), only the m/z 189 ions derived from the meta and para isomers underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Lehner et al also observed the Na‐adduct product ion in an ivermectin spectrum, but its structure was not proposed . Sodiated OE structures are very uncommon in ESI, and our literature search only found a report describing that the benzene carboxylate sodium salt can form a cation radical by elimination of Na • . However, there is no evidence in the mass spectrum of ivermectin for the addition of more than one sodium to justify the ejection of Na • .…”
Section: Resultsmentioning
confidence: 93%
“…Lehner et al also observed the Na‐adduct product ion in an ivermectin spectrum, but its structure was not proposed . Sodiated OE structures are very uncommon in ESI, and our literature search only found a report describing that the benzene carboxylate sodium salt can form a cation radical by elimination of Na • . However, there is no evidence in the mass spectrum of ivermectin for the addition of more than one sodium to justify the ejection of Na • .…”
Section: Resultsmentioning
confidence: 93%
“…For example, we reported previously that the alkali adducts of the disodium salts of phthalic acids undergo specific fragmentation reactions in which the charge‐imparting sodium atom is often retained . In a subsequent survey of other dicarboxylic acid compounds, we noted that metal adducts of oxalate salts fragment in a similar manner.…”
Section: Introductionmentioning
confidence: 87%
“…However, for liquid chromatography mass spectrometry (LC‐MS), the acidic modifiers that are added to the mobile phase for better chromatography of acidic analytes cause a high degree of matrix interference and suppress the ionization to a certain extent in the negative mode. Although many applications of negative‐mode LC‐MS have been reported recently, the majority of the procedures for quantitative profiling of acidic compounds and their salts have been conducted traditionally by positive‐mode mass spectrometry . The collision‐induced fragmentation spectra of salt‐metal adducts are often different from those of the corresponding proton adducts, providing additional structural information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations